Waste worlds : inhabiting Kampala's infrastructures of disposability - Doherty, Jacob, 1984- (Atelier (Oakland, Calif.), 2022)
"Uganda's capital, Kampala, is undergoing dramatic urban transformations as its new technocratic government seeks to clean and green the city. Waste Worlds tracks the dynamics of development and disposability unfolding amid struggles over who and what belongs in the new Kampala. Garbage materializes these struggles. In the densely inhabited social infrastructures in and around the city's waste streams, people, places, and things become disposable but conditions of disposability are also challenged and undone. Drawing on years of ethnographic research, Jacob Doherty illustrates how waste makes worlds, offering the key intervention that disposability is best understood not existentially, as a condition of social exclusion, but infrastructurally, as a form of injurious social inclusion"--